Change and archaeology - Crellin, Rachel, author.
1 online resource (xvi, 250 pages)
Keywords: "Change and Archaeology explores how archaeologists have historically described, interpreted, and explained change and argues that change has been under-theorised. The study of change is central to the discipline of archaeology but change is complex and this makes it challenging to write about in nuanced ways that effectively capture the nature of our world. Relational approaches offer archaeologists more scope to explore change in complex and subtle ways. Change and Archaeology presents a posthumanist, post-anthropocentric, new materialist approach to change. It argues that our world is constantly in the process of becoming and always on the move. By recasting change as the norm rather than the exception and distributing it between both humans and non-humans this book offers a new theoretical framework for exploring change in the past that allows us to move beyond block-time approaches where change is located only in transitional moments and periods are characterised by blocks of stasis. Archaeologists, scholars, anthropologists and historians interested in the theoretical frameworks we use to interpret the past will find this book a fascinating new insight into the way our world changes and evolves. The approaches presented within will be of use to anyone studying and writing about the way societies and their environs move through time"--